Developing Listening Log Based-Book for the Third Semester Students of English Education Department at Muhammadiyah Kotabumi University - Susilowati, Rini; Hardiyanto, Asep (Universitas Negeri Semarang, 2022)
Listening considered as difficult skill and some problems often experienced by the students which are understanding difficult and new words used by native speakers and connect the meaning into certain message, following the fast speed of speaking of native speakers, understanding different accents and pronunciation of native speakers. Referring to the problems which also experienced by the third semester students of English Education Department at Muhammadiyah Kotabumi university, the researchers conducted a research by applying Research and Development method. The researchers designed listening log-based book as learning source for the students. Forty students became the research subject and the researchers used test and interview to collect the data. The book completed with theories related to material in listening comprehension, some effective strategies to be applied in different listening material and some exercises. The book has been validated, revised and tried out to the students. Based on the result of book try out it was found that the book was effective to reduce learning barrier during listening comprehension course in the class.